1975
DOI: 10.4141/cjas75-016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Calcium and Phosphorus on Growth and Skeletal Development of Growing Swine

Abstract: and phosphorus on growth and skeletal development ofgrowing swine. Can. J. Anim. A factorial design with three levels of calcium, three levels of phosphorus, two breeds and both sexes (72 pigs) was employed to study calcium and phosphorus deficiencies and imbalances in swine fed from 22 kg ro 90 kg. Dietary levels of both minerals were 50, 100 and l5OVa rsf National Academy of Sciences-National Research Council (NAS-NRC) recommendations (1968

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
15
0
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 11 publications
5
15
0
1
Order By: Relevance
“…A rise in plasma PTH levels is also observed after intravenous infusion of EGTA or EDTA in cows (Blum and Fischer, 1975 ;Sherwood et al, 1966 ;Saeki and Hayashi, 1976 (Ramberg et al, 1976. ) Histological findings in pigs have suggested that a low Ca : P ratio (0.5) induces an increase in parathyroid activity as compared with that observed using a normal Ca : P ratio (1.2) (Nunez, Krook and Whalen, 1976) ; this agrees with a previous observation of Doige, Owen and Mills (1975). In contrast, we found no rise in plasma PTH level with a Ca-P ratio of 0.5 (Pointillart, Garel and Gu6guen, 1978b) (Doige et a/., 1975 ;Horvath and Papp, 1972 ;Stockland and Blaylock, 1973) (Chen, Toribara and Warner, 1956).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…A rise in plasma PTH levels is also observed after intravenous infusion of EGTA or EDTA in cows (Blum and Fischer, 1975 ;Sherwood et al, 1966 ;Saeki and Hayashi, 1976 (Ramberg et al, 1976. ) Histological findings in pigs have suggested that a low Ca : P ratio (0.5) induces an increase in parathyroid activity as compared with that observed using a normal Ca : P ratio (1.2) (Nunez, Krook and Whalen, 1976) ; this agrees with a previous observation of Doige, Owen and Mills (1975). In contrast, we found no rise in plasma PTH level with a Ca-P ratio of 0.5 (Pointillart, Garel and Gu6guen, 1978b) (Doige et a/., 1975 ;Horvath and Papp, 1972 ;Stockland and Blaylock, 1973) (Chen, Toribara and Warner, 1956).…”
supporting
confidence: 88%
“…Our experiments in pigs led to the conclusion that CT secretion is more sensitive than PTH secretion to changes in plasma calcium level. Care et al (1968) (Horvath and Papp, 1972 ;Doige, Owen and Mills, 1975 ;Stockland and Blaylock, 1973 Doige, Owen and Mills (1975) In pigs we must also emphasize the importance of the relationships between the plasma concentrations of magnesium and CT already observed (Pointillart, Garel and Gu6guen, 1978b). In the present experiments, during the control period and the last period of the low calcium diet, an inverse relationship was established between magnesemia and plasma CT levels.…”
mentioning
confidence: 66%
“…Boyd et al (1983) verificaram que a disponibilidade de fósforo no milho com alta umidade foi semelhante quando determinada com base na resistência à quebra de osso ou na atividade de fosfatase alcalina como critério de resposta. Por outro lado, Doige et al (1975) observaram que os níveis de fosfatase alcalina no soro apresentam pouco valor no diagnóstico de deficiência de cálcio ou fósforo. Koch & Mahan (1986) e Engstron et al (1985) encontraram efeito linear significativo na concentração de fósforo inorgânico no soro sangüíneo de suínos em terminação recebendo níveis crescentes de fósforo dietético.…”
Section: Resultsunclassified
“…According to Laflamme and Jowsey (1972), dogs maintained on high phosphorus diet for 10 months exhibited a decrease in plasma phosphate level 12 weeks after the beginning of treatment, whereas plasma calcium level was unchanged. However, serum inorganic phosphate increased in pigs fed over a long period (from 20 to 90 kg ; 3-4 months) (Bayley et al, 1975 ;Doige, Owen and Mills, 1975) ; a trend to hypocalcemia was also observed (Nielsen et al, 1971). A long-term treatment of phosphate supplements in rabbits was without effect on plasma phosphate, but decreased plasma calcium level (Jowsey and Balasubramanian, 1972).…”
mentioning
confidence: 99%